CIVIL SERVANT CAREER DEVELOPMENT STRATEGY IN THE TNI ENVIRONMENT - Riska Riskawati; Purnomo Yusgiantoro; Amany Burhanuddin Umar Lubis; Herlina Juni Risma Saragih (Jurnal Scientia, 2023)
A career is the journey of an employee's life in a workplace that begins when they are hired and ends when they retire. Every employee hopes that his career in an organization always goes in a better direction. In accordance with the formulation of the research problem, the purpose of this research is to find out how the career development of civil servants occurs in the TNI organization. The research method used in this study is qualitative research with a descriptive analysis approach. Referring to what Cresswell (2010) said, qualitative research is research to explore and understand the meaning that a number of individuals or groups of people ascribe to social or humanitarian issues. Therefore, this research activity is designed to collect, describe, and interpret data about the situation experienced, certain relationships, activities, views, attitudes, or trends appearing in the ongoing process. According to real results and facts, the performance of PNS TNI has been very good. However, career development needs to be improved due to several factors that may not be sufficient. Therefore, it is necessary to adopt a strategy so that the careers of PNS TNI can develop and have optimal competence per organizational needs.